2021
DOI: 10.1021/acs.orglett.1c02646
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Trifluoromethylated Pyrazolidines, Pyrazolines and Pyrazoles via Divergent Reaction of β-CF3-1,3-Enynes with Hydrazines

Abstract: Three types of trifluoromethylated pyrazolidines, pyrazolines, and pyrazoles can be synthesized via divergent reaction of β-CF3-1, 3-enyne with hydrazines. The reaction with simple hydrazine monohydrate or sulfonyl hydrazines as nucleophiles produces 1,3,4-trisubstituted pyrazolines, whereas the reaction with acetyl hydrazine as nucleophiles affords 1,4,5-trisubstituted pyrazolidines. Using phenylhydrazine or tert-butylhydrazine as a reaction partner, the products are easily oxidized to form 1,4,5-trisubstitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…To inspect our hypothesis, we commenced our study by employing 4-phenyl-2-trifluoromethyl-1,3-conjugated enyne 1a with malononitrile 2a to CF 3 -substituted allenes in the presence of various bases. According to previous reports, organic bases are suitable for the synthesis of CF 3 -substituted compounds, because they can suppress the defluorination process by avoiding the interaction of fluorine with metal. , Meanwhile, silver catalyst can accelerate the formation of allene intermediates and increase the electrophilicity of alkynes; therefore, we chose Ag/DBU as the initial catalyst system to achieve this transformation. It is a pity that CF 3 -substituted CN-functionalized allenes could not be isolated, despite that CF 3 -substituted allenes could be detected within 10 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To inspect our hypothesis, we commenced our study by employing 4-phenyl-2-trifluoromethyl-1,3-conjugated enyne 1a with malononitrile 2a to CF 3 -substituted allenes in the presence of various bases. According to previous reports, organic bases are suitable for the synthesis of CF 3 -substituted compounds, because they can suppress the defluorination process by avoiding the interaction of fluorine with metal. , Meanwhile, silver catalyst can accelerate the formation of allene intermediates and increase the electrophilicity of alkynes; therefore, we chose Ag/DBU as the initial catalyst system to achieve this transformation. It is a pity that CF 3 -substituted CN-functionalized allenes could not be isolated, despite that CF 3 -substituted allenes could be detected within 10 min.…”
Section: Resultsmentioning
confidence: 99%
“…At the outset, for 1,3-enyne skeletons, cycloaddition reactions and 1,2-dicarbofunctionalization were developed to obtain CF 3 -containing products by Gevorgyan, Trost, Song, Liu, and others, respectively . Next, given the electron-withdrawing effect of the trifluoromethyl group onto 1,3-enyne skeletons, Zhang and Xiao successively reported a series of cascade nucleophilic addition–cyclization reactions of 2-trifluoromethyl-1,3-enynes with various bisnucleophiles to afford trifluoromethylated heterocycles and cyclopentenes . Later, protoborylation and diborylations of 2-trifluoromethyl-1,3-enynes were explored by Cao, Song, and Xu to synthesize various CF 3 -containing borylated compounds, in which the high degree of selectivity was controlled by ligands .…”
Section: Introductionmentioning
confidence: 99%
“…The reaction mechanisms are in good agreement with those reported in previous studies. [64][65][66][67][68][69] By inspecting activation energies in paths connecting the reactant and the product for the chemical systems shown in Figure 4 in their respective reaction networks, we have found that the minimum energy paths agree with the expected ones described to allow for posterior successful optimizations of transition states with the higher DFT-B3LYP level of theory.…”
Section: Reaction Network Generation With Graph Theorymentioning
confidence: 89%
“…For example, Coumain and its derivatives, which contain pyran structures, widely exist in natural products and possess promising antitumor and antimicrobial activities. , Erythromycin is a commercially available antiphlogistic medicine that has been widely used in the curation of purulent skin diseases such as impetigo, small burns, and ulcer infections . Both pyrasulfotole and pyraclostrobin contain pyrazole fragments and have been respectively registered as excellent herbicides and fungicides for agrichemical applications. , On the basis of the fantastic bioactivities of both pyran and pyrazole structures, a diversity of unprecedented molecules combining the two fragments has been designed, synthesized, and evaluated . Among the various chemical entities that connect the pyran and the pyrazole structures together, pyrano­[2,3- c ]­pyrazoles represent one class of the most impressive and promising architectures exhibiting excellent bioactivities (Figure b) .…”
mentioning
confidence: 99%